Structural organization of sacred landscapes - Mishchenko, Olena V. (Oles Gonchar Dnipropetrovsk National University, 2019)
The article presents the results of scientific developments concerning the structural organization of sacred landscapes. The methodological basis of the study is the concept of constructive-geographic analysis, which is based on the approaches of the natural and the humanitarian sciences. The system approach to the study of sacred landscapes as a holistic organized territorial structure and a set of methods is used in this work, in particular: structural and logical generalization and system analysis, comparative and geographical, historical and geographical. The author considers the significance of the notion of sacral landscape more widely than religious, and considers it a natural, natural-anthropogenic, anthropogenic system associated with certain symbols of life, myths, significant events, religious feelings that are of great importance to a person or group of people and requires special respect and protection. The structural organization of all sacred landscapes is characterized by its properties and spatial structure and is closely connected with their social and functional purpose. As a result, such territorial systems can be divided into: confessional, taphal, actival, abnormal. The sacred landscape is characterized by polystructurenes, that is, the presence of spatial, temporal, morphological structure. In the spatial structure of the sacral landscape, the following components can be distinguished: a sacred object, anthropogenic and technogenic component, a landscape structure, a person with her spiritual experience. In addition, such a structure has a hierarchical structure, where individual, local, regional, national, global levels can be distinguished. The article presents the peculiarities of the temporal structure of sacral landscapes and outlines the external, internal, and the functioning time. Particular attention is paid to the characteristic of internal time, where one can distinguish the following phases of development: the formation of a natural, natural or anthropogenic landscape; the creation of a spiritual component; loss of sacred human perception of a natural, natural or anthropogenic landscape; the disappearance of the natural, natural anthropogenic landscape. Taking into account the morphological structure of the sacred landscape, it is substantiated that religious objects serving as markers of sacred landscapes can not correspond to one or another morphological unit of the landscape, that is, to completely repeat its outlines and boundaries. However, there is a correlation between the type of landscape landscape and the features of the sacred object that was formed there.
Keywords: sacred landscape; sacred object; structure